Improving pharmacology course challenge through implementation of the golden course standard - Hansi Zhang; Fengying Guan; Ming Zhang; Yingshi Ji; Jing Li (Guoji laonian yixue zazhi)
This study aims to explore how to deepen the construction of pharmacology course challenges based on the "golden course" standards and evaluate its application effects in improving course quality and students' comprehensive abilities. By integrating cutting-edge technologies with disciplinary knowledge, multidisciplinary teaching content was designed to promote curriculum innovation. A teaching method combining a three-tiered interactive model with case analysis was adopted to enhance student engagement in class. The study also incorporated virtual simulation experiments and innovative practices to further strengthen the integration of theory and practice, helping students better apply their knowledge to real-world scenarios. A comprehensive assessment of teaching effectiveness was conducted to scientifically measure students' learning outcomes and capability improvements. Through optimized instructional design, intensified skill training, enriched practical approaches, and balanced evaluation mechanisms, this study not only significantly enhanced course quality and student abilities but also provided valuable practical insights for the development of higher education.